Neurotransmitter Interactions and Cognitive Function - Pokorski, Mieczyslaw; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
A host of neurotransmitters and neuroactive substances underlies respiratory regulation in health and disease. The centerpiece of investigations regarding adaptation to hypoxia and sensorial perception has been the dopaminergic system. It is now clear that a complex interaction among various neuroactive substances, rather than a single one, forms the basis of respiratory changes. The research on neurotransmitter interactions provides the knowledge of how the brain functions and a new level of understanding of mind-to-body connection, which opens up avenues for novel therapeutic interventions.
Inherited Disorders of Brain Neurotransmitters: Pathogenesis and Diagnostic Approach -- Inhibition of Peripheral Dopamine Metabolism and the Ventilatory Response to Hypoxia in the Rat -- Adaptation of Olfactory Threshold at High Altitude -- Guanosine Protects Glial Cells against 6-Hydroxydopamine Toxicity -- Chemoresponsiveness and Breath Physiology in Anosmia -- Cognitive Functioning of the Prelingually Deaf Adults -- Hypoxia-Related Brain Dysfunction in Forensic Medicine -- Does Health Status Influence Acceptance of Illness in Patients with Chronic Respiratory Diseases?.
Keywords: Medicine; Human physiology; Vaccines; Neurosciences; Forensic medicine; Biomedicine; Human Physiology; Vaccine; Neurosciences; Medicine/Public Health, general; Forensic Medicine; Electronic books